2017
DOI: 10.1038/s41598-017-11810-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of metronomic capecitabine for treatment of recurrent hepatocellular carcinoma after liver transplantation

Abstract: The management of recurrent hepatocellular carcinoma untreatable with surgical options is based on systemic therapy with sorafenib. Due to the high rates of adverse events connected to the therapy with sorafenib, metronomic capecitabine seems a promising strategy for these patients. We analyzed the data of 38 patients with hepatocellular carcinoma recurrent after liver transplantation performed at our center. We compared the outcome of 17 patients receiving metronomic capecitabine versus 20 patients experienci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…As a classic chemotherapeutic drug, a large number of clinical studies have confirmed the efficacy of capecitabine in the field of HCC ( 4 , 6 ). Moreover, there is evidence that CAP may have an immunosuppressive effect, but this still needs to be confirmed by experiments ( 3 ). Therefore, we chose metronomic chemotherapy (a new type of chemotherapy featuring low-dose, uninterrupted, and continuous administration) dose or maximum tolerated dose of CAP to treat normal mice by oral gavage to explore the feasibility of CAP as a potential immunosuppressive agent ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a classic chemotherapeutic drug, a large number of clinical studies have confirmed the efficacy of capecitabine in the field of HCC ( 4 , 6 ). Moreover, there is evidence that CAP may have an immunosuppressive effect, but this still needs to be confirmed by experiments ( 3 ). Therefore, we chose metronomic chemotherapy (a new type of chemotherapy featuring low-dose, uninterrupted, and continuous administration) dose or maximum tolerated dose of CAP to treat normal mice by oral gavage to explore the feasibility of CAP as a potential immunosuppressive agent ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have confirmed that CAP also has a good therapeutic effect on hepatocellular carcinoma (HCC) ( 3 6 ). In 2017, Ravaioli et al found that CAP metronomic chemotherapy achieved a 1-year survival rate similar to sorafenib, and that there was no acute rejection during treatment in patients with HCC recurrence after liver transplantation ( 3 ). Their findings suggested that CAP may be a potential drug with both immunosuppressive and anti-cancer effects, which has important clinical application value in liver transplantation patients with HCC.…”
Section: Introductionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metronomic capecitabine (MC) has been tested as in first and in second line treatment for HCC patients by several studies, which demonstrated a good anticancer activity as well a very low rate of toxicities 21 24 . Also, MC may be effective and well tolerated in recurrent HCC after liver transplantation 25 . Nevertheless, none of these studies provided information about the potential effect of MC in CP-B HCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Capecitabine administration according to a standard (or reduced standard) schedule has been evaluated in the postoperative adjuvant setting after curative HCC resection [ 6 ], in advanced disease [ 7 ], and in recurrent HCC after liver transplantation [ 8 ]. In a small randomized controlled trial among patients with HCC, 30 controls treated with best supportive care (BSC) were compared with 30 subjects who received 2 weeks of capecitabine at 1000 mg/m 2 , twice a day, followed by 1 week without treatment for a total of 4–6 cycles [ 6 ].…”
Section: Introductionmentioning
confidence: 99%